2016
DOI: 10.1016/j.bjid.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of tuberculosis in patients treated for hepatitis C chronic infection

Abstract: Brazil is one of the 22 countries that concentrates 80% of global tuberculosis cases concomitantly to a large number of hepatitis C carriers and some epidemiological risk scenarios are coincident for both diseases. We analyzed tuberculosis cases that occurred during α-interferon-based therapy for hepatitis C in reference centers in Brazil between 2001 and 2012 and reviewed their medical records. Eighteen tuberculosis cases were observed in patients submitted to hepatitis C α-interferon-based therapy. All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
0
14
1
2
Order By: Relevance
“…The disease is a leading cause of mortality worldwide. TB is one of the immediate priorities of the World Health Organization (WHO), especially in countries with a low socioeconomic status (de Oliveira Uehara et al, 2016;Viney et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The disease is a leading cause of mortality worldwide. TB is one of the immediate priorities of the World Health Organization (WHO), especially in countries with a low socioeconomic status (de Oliveira Uehara et al, 2016;Viney et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other vulnerable groups are patients under treatment for rheumatoid arthritis, inflammatory bowel disease, kidney disease, diabetes and individuals with organ transplant [2]. Recently, it has been highlighted that there is higher TB incidence in patients treated for HCV infection [3]. In this report, analysis was done on TB incidence during interferon-based treatment for hepatitis C. The data showed that most of the HCV positive patients (89%) were treated with double therapy, i.e.…”
mentioning
confidence: 97%
“…genotype 3. As interferon based treatment could leads to TB reactivation, the higher burden of TB in Pakistan might be explained by de Oliveira Uehara et al [3]. In 2009, Pakistan ranks 8th in the world in term of TB burden and share about 44% of tuberculosis burden in the Eastern Mediterranean region [9].…”
mentioning
confidence: 99%
“…Dessa forma, esses dados demonstram a importância de se buscar a presença de distúrbios psiquiátricos entre indivíduos infectados pelo vírus da hepatite C, para que assim possam ser trabalhadas medidas de prevenção para eventos que podem, como visto, levarem a um incremento da morbimortalidade.No presente estudo, as infecções estiveram associadas a um risco quase três vezes maior de morte em indivíduos positivos para o HCV. Uma associação entre a infecção pelo HCV e risco aumentado para infecções bacterianas já foi relatada anteriormente[122][123][124][125][126] . Tuberculose, pneumonia adquirida na comunidade ou infecções bacterianas entre pacientes em hemodiálise são muito mais frequentes em indivíduos infectados pelo HCV[122][123][124][125][126] .…”
unclassified
“…Uma associação entre a infecção pelo HCV e risco aumentado para infecções bacterianas já foi relatada anteriormente[122][123][124][125][126] . Tuberculose, pneumonia adquirida na comunidade ou infecções bacterianas entre pacientes em hemodiálise são muito mais frequentes em indivíduos infectados pelo HCV[122][123][124][125][126] . A coinfecção com o HIV e o uso de drogas injetáveis também são mais comuns em pacientes infectados pelo HCV e podem levar a maiores taxas de mortalidade por sepse15 .…”
unclassified